The role of remittances from Syrian expatriates to support the stability of the exchange rate of the Syrian pound (Damascus University Journal for legal sciences, 2024)
The role of the national currency in international commercial transactions is highlighted through the so-called “exchange process”، which is the process of replacing the national currency with the foreign currency that is usually used in international commercial and financial transactions. These transactions are carried out according to a certain price، in which the value of the foreign currency exchanged with the currency of the national state is determined، which is called the "exchange rate".The exchange rate is the main tool that has a direct impact on the relationship between domestic prices and external prices، especially when it comes to encouraging exports and providing imports. It is also an important way to influence the allocation of financial resources between economic sectors، the profitability of export industries and the cost of imported materials.Remittances from expatriates to their home countries are of great importance at the level of the global economy on the one hand، and the local economy of the recipient country on the other hand، as they constitute a good percentage of the total cash flows into the country، and provide a source of financing for the banking system، by attracting these remittances and returning Use them in financing channels and bank lending.On the other hand، the continued flow of remittances from expatriates also has negative effects، as it exerts pressure on the exchange rate of the national currency، and enhances the consumer tendency of families and recipient groups.In this research، will be studying The role of remittances from Syrian expatriates to support the stability of the exchange rate of the Syrian pound، during of the economic crisis that Syria has been experiencing since 2011 to date.
Keywords: Remittances; exchange rate of the Syrian pound; Syrian expatriates